2013
DOI: 10.1007/s13238-013-2119-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulatory function of abundant immune-related microRNAs in microvesicles from bovine colostrum

Abstract: Colostrum provides essential nutrients and immunologically active factors that are beneficial to newborns. Our previous work demonstrated that milk contains large amounts of miRNA that is largely stored in milk-derived microvesicles (MVs). In the present study, we found that the MVs from colostrum contain signifi cantly higher levels of several immune-related miRNAs. We hypothesized that the colostrum MVs may transfer the immune-related miRNAs into cells, which contribute to its immune modulatory feature. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
151
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(164 citation statements)
references
References 26 publications
13
151
0
Order By: Relevance
“…Extracellular miRNAs were identified in a broad range of biological fluids (Pegtel et al, 2011;Huang et al, 2013;Kropp et al, 2014;Baglio et al, 2015;Dismuke et al, 2015;Wu et al, 2015). Apart from plasma, circulating miRNAs in milk are also intensely studied (Izumi et al, 2012;Kuruppath et al, 2013;Sun et al, 2013;Alsaweed et al, 2016c, b, a;Benmoussa et al, 2016;Xi et al, 2016).…”
Section: Extracellular Mirnas In Mammals and Their Transfermentioning
confidence: 99%
“…Extracellular miRNAs were identified in a broad range of biological fluids (Pegtel et al, 2011;Huang et al, 2013;Kropp et al, 2014;Baglio et al, 2015;Dismuke et al, 2015;Wu et al, 2015). Apart from plasma, circulating miRNAs in milk are also intensely studied (Izumi et al, 2012;Kuruppath et al, 2013;Sun et al, 2013;Alsaweed et al, 2016c, b, a;Benmoussa et al, 2016;Xi et al, 2016).…”
Section: Extracellular Mirnas In Mammals and Their Transfermentioning
confidence: 99%
“…The constitution of miRNAs in milk varies among different species (Hata et al, 2010;Munch et al, 2013;Izumi et al, 2014), the lactation period (Chen et al, 2010), and maternal dietary manipulation (Hata et al, 2010). Moreover, some miRNAs that are abundant in milk have been evidenced for their important functional roles in various biological processes, including immune response (Kosaka et al, 2010;Sun et al, 2013), postnatal growth (Melnik et al, 2013), and lipid metabolism (Fernández-Hernando et al, 2011). Recently, miRNAs in milk have been studied as potential biomarkers for milk quality control (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several extraction methods have been used in recent studies describing milk miRNAs (Izumi et al, 2013;Sun et al, 2013). Current protocols for isolation of milk miRNAs can be divided into two categories that are mainly distinguished by whether there is an exosome enrichment step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors found that the expression of several miRNAs is altered by a perturbed maternal diet, particularly following a high-fat intake. Furthermore, a recent study has shown that colostrum-derived miRNAs are taken up in vitro by macrophages and modulate their immune activities, such as migration and cytokine secretion (Sun et al, 2013). Collectively, although direct in vivo evidence is still lacking for the physiological relevance of milk miRNAs, accumulating reports strongly suggest their protective roles against early infections in infants.…”
Section: Exosomal Mirna-mediated Regulation Of the Immune Systemmentioning
confidence: 99%